Kajian in Silico Daun Sungkai (Peronema canescens) dalam Menghambat Enzim lanosterol 14-Î± demethylase Jamur Candida albicans - Nurul Istiqomah; Safitri Fatikasari; Ariani H. Hutuba (Indonesian Journal of Pharmaceutical Education, 2023)
Candida albicans (C. albicans) is a fungus that causes candidiasis. C. albicans has the enzyme Lanosterol 14- Î± demethylase. Lanosterol 14-Î±-demethylase has bioactivity in converting lanosterol to ergosterol, a special sterol found in fungal membranes, which mediates membrane permeability and fluidity. One way to treat candidiasis is to use traditional medicinal plants. Sungkai (Peronema canescens) can be used as an anti-fungal medicine. Drug development efforts can be done using the In silico method. Objectives of this study was to determine the interaction between terpenoid, flavonoid, and phenol compounds in Sungkai leaves against Lanosterol 14-Î± demethylase in Candida albicans. The research design used was a pre-experimental one-shot case study. Toxtree software was used to test the toxicity of compounds. Test for compound potency using the Pass Online webserver. Docking molecular using PyRx software. Visualization of docking results using Discovery Studio 2019 Software. Physicochemical test of compounds using Lipinski Test. The results showed that the compounds that had a low risk of toxicity were butanoic, catechol, guaiacol, hydroquinone, isopropanol, methanoic acid, palmitic acid, and phytol. Compounds that have anti-fungal activity based on Pharma-expert analysis are butanoic acid, genkwanin, guaiacol, hydroquinone, isopropanol, palmitic acid, and phytol. Compounds that have hydrogen bonds and binding affinity value 10 and RMSD value 2 are butanoic acid, catechol, genkwanin, guaiacol, hydroquinone, isopropanol, methanoic acid, palmitic acid, and quinic acid compounds. These compounds are thought to inhibit the Lanosterol 14-alpha demethylase enzyme in C. albicans. Compounds that comply with Lipinski's rules are anthocyanin and genkwanin compounds. The groups of compounds found in Sungkai leaves that have antifungal activity are the terpenoids, flavonoids, and phenols.